2017
DOI: 10.1002/aoc.4043
|View full text |Cite
|
Sign up to set email alerts
|

An efficient catalytic method for the synthesis of pyrido[2,3‐d]pyrimidines as biologically drug candidates by using novel magnetic nanoparticles as a reusable catalyst

Abstract: A convenient method for the synthesis of pyrido[2,3‐d]pyrimidines by using the novel nano‐magnetic silica‐bonded S‐sulfonic acid[Fe3O4@SiO2@(CH2)3S–SO3H] as an efficient and recyclable catalyst under neat conditions is described. The major advantages of the present methodology are high yield, short reaction time, and reusability of the catalyst. Furthermore, the nano‐magnetic silica‐bonded S‐sulfonic acid was fully characterized by using various techniques such as FT‐IR, TG/DTG, DTA, EDX, μXRF, XRD, HRTEM, SEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…Later, in 2016, urea (fertilizer)-based ionic liquid (IL)-stabilized Fe 3 O 4 MNPs were successfully used as catalysts for the synthesis of 179b in excellent yields without the use of any solvent at 60 C. 193 Further, in 2017, Zarei et al reported the synthesis of 183 using silica-bonded S-sulfonic acid-supported ferromagnetic MNPs without solvent at 100 C using 2, 29a and 2,4-diamino-6-hydroxypyrimidines. 194 Maleki et al also reported the similar synthesis of 179b using biodegradable and eco-friendly catalysts such as cellulose-based nanocomposites anchored on Fe 3 O 4 in water at rt in 76-98% yield. 195 Pal et al reported the one-pot multicomponent synthesis of dihydropyrano [2,3- .…”
Section: Fenp-catalyzed Synthesis Of Heterocyclesmentioning
confidence: 94%
“…Later, in 2016, urea (fertilizer)-based ionic liquid (IL)-stabilized Fe 3 O 4 MNPs were successfully used as catalysts for the synthesis of 179b in excellent yields without the use of any solvent at 60 C. 193 Further, in 2017, Zarei et al reported the synthesis of 183 using silica-bonded S-sulfonic acid-supported ferromagnetic MNPs without solvent at 100 C using 2, 29a and 2,4-diamino-6-hydroxypyrimidines. 194 Maleki et al also reported the similar synthesis of 179b using biodegradable and eco-friendly catalysts such as cellulose-based nanocomposites anchored on Fe 3 O 4 in water at rt in 76-98% yield. 195 Pal et al reported the one-pot multicomponent synthesis of dihydropyrano [2,3- .…”
Section: Fenp-catalyzed Synthesis Of Heterocyclesmentioning
confidence: 94%
“…In recent years, there has been a rapid growth in the development of novel supported compounds such as supported catalysts, reagents, sensors and adsorbents. [1][2][3][4][5][6][7] Therefore, nanoparticles have been widely used as solid supports for the immobilization of homogeneous catalysts. [8][9][10] For example, silica materials, [11] polymers, [12] graphene oxide, [13][14][15][16] carbon nanotubes, [17] iron oxide, [18] ionic liquids, [19,20] boehmite nanoparticles, [21,22] biochar, [23] magnetic nanoparticles, [24][25][26] etc.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, surface modification of magnetic nanoparticles is an allowable method to eliminate the giant gap between homogeneous and heterogeneous catalysts 63–67 . Sulfuric acid is used as an efficient and irretrievable Brønsted–Lowry acid catalyst to generate different kinds of chemical materials 68–71 . Sulfonation with sulfosalicylic acid as a suitable, quick, and executable system has attracted great attention for the production of heterogeneous catalysts 72 .…”
Section: Introductionmentioning
confidence: 99%